The Association between Vitamin D Deficiency and Chronic Tonsillitis in Children: an Evidence Based Case Reports - Ardian Sandhi Pramesti; Gabriella Nurahmani Putri; Steffi Sonia (Archives of The Medicine and Case Reports, 2021)
Background: vitamin D has an important influence on the host’s immune system by modulating both innate and adaptive immunity and regulating the inflammatory cascade. Vitamin D deficiency may be related with reduced immunomodulation, specifically in preventing the occurrence of chronic tonsillitis. Objective: to identify the association between vitamin D deficiency with chronic tonsillitis in pediatric patients. Methods: the search was conducted with advanced searching on PubMed® and Cochrane® according to the clinical question. The screening of title and abstract using inclusion and exclusion criteria, double filter, and reading full text led to six useful articles. The selected studies were critically appraised for validity, importance, and applicability. Results: three original articles were eligible for this evidence-based case report. All studies were considered to have good validity. All three studies reported an increased risk of chronic tonsillitis with the vitamin D deficiency and/or insufficiency. Conclusion: Vitamin D deficiency may be associated with the increased risk of chronic or recurrent tonsillitis in children.